Devotional Politics as States of Exception: Santa Muerte’s Challenge to Church and State Sovereignties - Blackwell, Brent Adam (Political theology, 2020)
In this paper, I argue that popular veneration of Santa Muerte challenges state and church sovereignty in Mexico. In turn, I look at “deviance” as a rich theoretical space through which to consider adoration of the saint among criminal and transgender communities and the ways in which she provides alternative experiences outside of the sovereign regulations of the church and the state. In so doing, I frame Santa Muerte as a “state of exception” and a “queer saint” because she subverts power and actualizes the margins as a site of empowerment and resists simplified constructions of sexuality and gender binaries. Amidst structural, political, and ecclesial oppressions, devotees find new forms of resistance and agency in the figure of Santa Muerte.